Fibrin Formed in Plasma is Composed of Fibers More Massive than those Formed from Purified Fibrinogen - Carr, Marcus E (Thrombosis and Haemostasis, 1988)
Reports of altered fibrin resulting from interactions with plasma proteins and cellular release products have raised the possibility that plasma fibrin may differ from purified fibrin. To investigate this possibility, the structures of thrombin-induced gels formed from platelet poor plasma and from purified fibrinogen were compared using turbidity and gel perfusion techniques. Plasma gels formed more slowly and were composed of fibers two to four times more massive than gels formed from purified fibrinogen. Increasing calcium concentration, decreasing ionic strength, decreasing thrombin concentration, or increasing fibrinogen concentration resulted in increasing fiber size. Addition of excess thrombin accelerated plasma gel formation and decreased gel fiber size, but did not totally eliminate the structural differences between the two systems. Thus, antithrombin activity, while possibly contributory, is not solely responsible for the altered gel structure. Penetration of plasma gels by fibrinolytic agents, egress to areas of injury by inflammatory cells, and gel removal by plasmin are processes at least partially dependent on gel fiber and pore size.
Keywords: Fibrin; Plasma; pH; Ionic strength; Calcium